Distribution of Competition Potential Between Native Ungulates and Free‐Roaming Equids on Western Rangelands. Issue 6 (1st February 2021) - Stoner, David C.; Anderson, Michael T.; Schroeder, Cody A.; Bleke, Cole A.; Thacker, Eric T.
ABSTRACT: Free‐roaming equids (i.e., feral horses [ Equus caballus ] and burros [ Equus asinus ]) are widely distributed and locally abundant across the rangelands of the western United States. The 1971 Wild Free Roaming Horse and Burro Act (WFRHBA) gave the Bureau of Land Management (BLM) and United States Forest Service (USFS) the legal authority to manage these animals on designated public lands. To fulfill this responsibility, federal agencies established an Appropriate Management Level (AML), defined as the number of horses or burros that can be sustained on a given management unit under prevailing environmental conditions and land uses. Although the WFRHBA specifies that feral equids must be managed in ecological balance with other land uses, including conservation of native wildlife, population control measures such as gathers, contraception, and adoptions have failed to keep pace with intrinsic growth rates. Over 80% of federally managed herds currently exceed prescribed population levels, making the potential for competition between native ungulates and feral equids a growing concern among state wildlife agencies. Mule deer ( Odocoileus hemionus ), pronghorn ( Antilocapra americana ), elk ( Cervus canadensis ), and bighorn sheep ( Ovis canadensis ) are of ecological and economic value to the states where they occur, and all exhibit some degree of distributional, habitat, or dietary overlap with horses or burros. Notwithstanding the scale of the problem, to date there have been no range‐wide assessments of competition potential among native and feral ungulates for space, forage, or water. To address this need, we compiled demographic, jurisdictional, and species occurrence data collected from 2010–2019 by federal and state agencies. We used these data to map the distributions of 4 native ungulate species across federal equid management units (FEMUS) in 10 western states ( n  = 174). We then made within‐state rankings of the 50 units that were ≥2 times over AML and encompassed ≥3 native ungulates. Collectively, FEMUs covered approximately 225, 000 km 2, representing 18% of all BLM and USFS lands in affected states. Each FEMU supported ≥1 native ungulate and 14% contained all 4. The degree of overlap between native and feral species varied by state, ranging from <1% for mule deer in Montana, to 40% for bighorn sheep in Nevada. Oregon had the largest proportion of units that supported all 4 native ungulates (58%), whereas Montana and New Mexico had the fewest equids, but all populations were over target densities. Despite the perception that the problem of equid abundance is limited to the Great Basin states, high intrinsic growth rates and social constraints on management practices suggest all affected states should monitor range conditions and native ungulate demography in areas where forage and water resources are limited and expanding equid populations are a concern. © 2021 The Wildlife Society. Abstract : The problems associated with equid abundance are not limited to the Great Basin states. High growth rates and social constraints on management practices suggest all states with feral equids should monitor range conditions and native ungulate demography to develop plans to mitigate competition between native and feral ungulates for limited resources.